Study of lift enhancing mechanisms via comparison of two distinct flapping patterns in the dragonfly sympetrum flaveolum - Chen, Y. H. (2015)
The computational fluid dynamic model of a live-sized dragonfly (Sympetrum flaveolum) hindwing is simulated according to the in-flight flapping motions measured in kinematic experiments. The flapping motion of the simulated wing is accomplished by dynamically re-gridding the wing-fluid mesh according to the established kinematic model for each flapping pattern. Comparisons between two distinct flapping patterns (double figure-eight and simple figure-eight) are studied via analysis of the aerodynamic forces and flow field structures. The result shows that additional lift is generated during supination and upstroke for the double figure-eight pattern, while maximum thrust is generated during pronation for the simple figure-eight pattern. In addition, through our comparisons of the different kinematics, we are able to reveal the mechanism behind the leading edge vortex stabilization prior to supination and the kinematic movement responsible for additional lift generation during supination. By increasing the translational deceleration during stroke-end rotations in the double figure-eight flapping pattern, a trailing edge vortex is formed which is stronger as compared to the single figure-eight flapping pattern, thus enhancing the lift.